Nutrigenetics, Nutrigenomics, and Selenium - Ferguson, Lynnette R.; Karunasinghe, Nishi (Frontiers in Genetics, 2011)
Selenium (Se) is an important micronutrient that, as a component of selenoproteins, influences oxidative and inflammatory processes. Its’ levels vary considerably, with different ethnic and geographic population groups showing varied conditions, ranging from frank Se deficiencies to toxic effects. An optimum Se level is essential for the maintenance of homeostasis, and this optimum may vary according to life stage, general state of health and genotype. Nutrigenetic studies of different Se levels, in the presence of genetic variants in selenoproteins, suggest that an effective dietary Se intake for one individual may be very different from that for others. However, we are just starting to learn the significance of various genes in selenoprotein pathways, functional variants in these, and how to combine such data from genes into pathways, alongside dietary intake or serum levels of Se. Advances in systems biology, genetics and genomics technologies, including genetic/genomic, epigenetic/epigenomic, transcriptomic, proteomic and metabolomic information, start to make it feasible to assess a comprehensive spectrum of the biological activity of Se. Such nutrigenomic approaches may prove very sensitive biomarkers of optimal Se status at the individual or population level. The premature cessation of a major human Se intervention trial has led to considerable controversy as to the value of Se supplementation at the population level. New websites provide convenient links to current information on methodologies available for nutrigenetics and nutrigenomics. These new technologies will increasingly become an essential tool in optimising the level of Se and other micronutrients for optimal health, in individuals and in population groups. However, definitive proof of such effects will require very large collaborative studies, international agreement on study design and innovative approaches to data analysis.